Angiographic Anatomy of External Iliac Arteries in the Sheep. (17th December 2015) - Joscht, M.; Martin, M.; Henin, M.; Nisolle, J. F.; Kirschvink, N.; Dugdale, A.; Godart, B.; Coulon, H.; Simon, V.; Hontoir, F.; Graffin, R.; De Raeve, Y.; et al.
Summary: External iliac artery atherosclerotic disease and aneurism occur in man. For treatment, imaging is required to facilitate minimally invasive introduction and advancement of stents within the intended vessels. Sheep are commonly used to test and improve stents. However, little information is published regarding the angiographic anatomy of the iliac arteries in the ovine species. The objective of this study was to describe the angiographic anatomy of the iliac arteries in the sheep. Computed tomography (CT) angiography and gross anatomical dissection were performed in, respectively, 10 and 43 adult ewes. Diameters and lengths of the arteries were measured. In comparison with man, salient anatomical differences were identified in the sheep: (1) the absence of common iliac arteries, (2) the common trunk at the origin of internal iliac arteries and (3) the location of the bifurcation of the external iliac arteries into femoral arteries in the pelvis (not in the limb). External iliac arteries in this series of sheep were 86 mm long in average and had a mean diameter of 7.5 mm. Lengths of arteries are only slightly different between man and sheep, while diameters are rather similar. Therefore, the sheep model appears to be sufficiently similar to man to test stent properties. This study provides useful reference images and measures of lengths and diameters of relevant arteries that could be applied to research with ovine models.